Studi Keanekaragaman Zooplankton Sebagai Bioindikator Kualitas Perairan Sungai Anyar (Anak Sungai Bengawan Solo) Surakarta - Aksiwi, Daniek Hayu; , Efri Roziaty, S.Si.,M.Si (2017)
Various activities found around the Anyar river such as construction project, domestic waste, animal husbandry, and fishing that keep continuing can change the physical, chemical, and biological condition in which influence through water quality and biota living there. The objective of this research is to find water quality based on variety index of zooplankton in Anyar river. The researcher used purposive sampling method by determined the three station that is station A the upstream areas that occurs the activities construction project, station B the middle areas of the occurrence of the existence of that settlement activity and station C the downstream areas that occurs the exixtence of project activities construction of rail and animal husbandry. The identification zooplankton result found 33 species from 20 genus and from the 7 main phylum such as Rotifera (11 species from 6 genus), arcomatigophora (9 species from 2 genus), Nematoda (2 species from 2 genus), Chiliophora (4 species from 4 genus), Protozoa (5 species from 4 genus), Chaetognatha (1 species from 1 genus), dan Arthropoda (1 species from 1 genus). Variety indeks (H') revolve between -2,70 to -3,04. It means the biota community is unstable caused by the water quality seriously contaminated.